Mathematical modelling and simulation of the mechanical component of the fully differential capacitive mems accelerometer using matlab/simulink environment - Holovatyy, А.; Teslyuk, V.; Panchak, R.; Koshyrets, S. (Видавництво Львівської політехніки, 2015)
Розроблено імітаційну модель механічної компоненти повністю диференційного ємнісного МЕМС акселерометра в середовищі MATLAB/Simulink. Модель дає змогу моделювати переміщення робочої маси, зміну ємностей вимірювальних конденсаторів чутливого елемента, чутливість мікродавача від прикладеного прискорення, а також проводити часовий аналіз інтегрального пристрою на системному рівні проектування. Simulation model of the mechanical component of the fully differential capacitive MEMS accelerometer has been developed using MATLAB/Simulink environment. The model allows to simulate movement of the proof mass, capacitance changes of the sense capacitors of the sensitive element, sensitivity of the sensor depending on the applied force of acceleration, and to perform the transient analysis of the integrated device at the system level of computeraided design.
Keywords: Мікроелектромеханічні системи (МЕМС); повністю диференційний ємнісний МЕМС акселерометер; прискорення; математичне моделювання; імітаційна модель; поведінковий аналіз; САПР; MATLAB/Simulink; Microelectromechanical systems (MEMS); fully differential capacitive MEMS accelerometer; acceleration; mathematical modeling; simulation model; transient analysis